Lifestyle Entrepreneurship for Poverty Reduction An analysis of the Covid-19 effect - Dias, Á.; Carvalho, João; Maria Rosario González-Rodríguez (62nd International Scientific Conference on Economic and Social Development, 2020)
Lifestyle entrepreneurship is characterized by a fading between the frontier of business and personal life. Furthermore, tourism lifestyle entrepreneurship is a way of reducing poverty. For this purpose, a multiple case study was conducted in the tourist region of Maranhão, Brazil, with two objectives: to identify how entrepreneurs create lifestyles for themselves and their tourist clients, and to analyze the strategies of lifestyle entrepreneurs to achieve a balance between lifestyle and profit. The results show that, despite the Covid-19 crisis that seriously affected tourism, the impact was moderate in the development of the lifestyle of entrepreneurs and clients. The drop in activity is explained by the suspension of flights and restrictions due to isolation, returning with great intensity immediately after the relaxation of sanitary measures. The synergy between profit and entrepreneurship as a lifestyle was positively shaken by social isolation, causing difficulties in the sustainability of the activity during the pandemic period. It was also verified that, even when there were no restrictions, the entrepreneurs were already engaged in seeking budgetary balance to keep their businesses active. It was concluded that these small businesses depend a lot on a greater flow of tourists who adhere to the lifestyle proposed by the enterprise to have positive results in their activities.